Bending Dynamics of DNA (Global Journal of Science Frontier Research, 2018)
It is here pointed out that the local opening of base pairs induces the formation of kinks which facilitates the bending of double helix. The conformational properties of DNA can be mapped onto the Heisenberg spin system and denaturation occurs through quantum phase transition (QPT) induced by a quench when the temperature effect is incorporated through the quench time . The nonequilibrium effect in QPT introduced through the quench generate defects like kinks end antikinks, the density of which depends on the quench time and hence on temperature. It is here argued that when we transcribe this result in the rod -like-chain (RLC) model of DNA, these defects lead to bends. This suggests that we have dynamical generation of kinks leading to the formation of bends during local denaturation.
Keywords: DNA; bends; kinks